Search for the Higgs boson H-2(0) at LHC in 3-3-1 model - Cieza Montalvo, J. E.; Gil Ramirez, R. J.; Ramirez Ulloa, G. H.; Rivasplata Mendoza, A. I.; Tonasse, M. D. [UNESP] (Amer Physical Soc, 2013)
present an analysis of production and signature of neutral Higgs boson (H-2(0)) on the version of the 3-3-1 model containing heavy leptons at the Large Hadron Collider. We studied the possibility to identify it using the respective branching ratios. Cross section are given for the collider energy, root S = 14 TeV. Event rates and significances are discussed for two possible values of integrated luminosity, 300 fb(-1) and 3000 fb(-1).